Traumatic Maculopathy 6 Months after Injury: A Clinical Case Report - Mendes, Sílvia (S. Karger AG, 2014)
PURPOSE: This study aims to report a case of traumatic maculopathy in a 12-year-old male following blunt trauma in his left eye (LE) who presented 6 months after injury. METHODS: Retrospective and descriptive case report based on data from clinical records, patient observation and analysis of diagnostic tests. RESULTS: A previously healthy, 12-year-old male presented for a routine visit with complaints of a 2-month history of decreased visual acuity in his LE. Six months before the initial visit, he suffered blunt trauma to the LE during a struggle and had no medical observation. At the visit, best-corrected visual acuity (BCVA) in the LE was counting fingers and in the right eye, it was 20/20. Fundus examination of the LE showed a central macular lesion of 1 disc diameter with fibrosis, increased retinal thickness and intraretinal hemorrhage. Optical coherence tomography showed disruption of the inner/outer segment (IS/OS) photoreceptor junction, increased reflectivity, cell infiltration of the retinal wall and retinal pigment epithelium detachment. Retinal thickness was 289 μm at the site of the lesion. A fluorescein angiogram revealed early impregnation and late diffusion. High-dose steroid pulse therapy (intravenous methylprednisolone 500 mg for 3 days and oral prednisolone 30 mg, tapering for 10 days) was done. LE BCVA increased to 20/200, and retinal thickness decreased by 71 μm 1 week after treatment. Off-label intravitreal triamcinolone (IVTA; 0.05 ml/2 mg) was administered 2 weeks after oral treatment in an attempt to achieve additional improvement. Three weeks after IVTA, LE BCVA improved to 20/150 and retinal thickness decreased by 10 μm. Three months after the initial visit, LE BCVA was 20/125 and retinal thickness 208 μm. CONCLUSION: We present a case of commotio retinae caused by an ocular blunt trauma 6 months before, with loss of BCVA. BCVA improved after oral steroids and IVTA. Nevertheless, fibrosis and disruption of the IS/OS junction in the macula limited the gain of BCVA.